Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/jb/mvab070
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of plasmodium ferredoxin Asp97Tyr mutant related to artemisinin resistance of human malaria parasites

Abstract: Mutation of Asp97Tyr in the C-terminal region of ferredoxin (PfFd) in the apicoplast of malaria parasites was recently reported to be strongly related to the parasite’s resistance to the frontline antimalarial drug, artemisinin. We previously showed that the aromatic amino acid in the C-terminal region of PfFd is important for the interaction with its electron transfer partner, Fd-NADP+ reductase (PfFNR). Here, the importance of the aromatic–aromatic interaction between PfFd and PfFNR was shown using the kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…one-tenth of the rate of ascorbate radical reduction and one-third of the rate of electron transfer to heterologous Fd-dependent nitrite reductase in a similar system in Ref. [ 8 ]). On the other hand, the addition of DHA (200–400 µM) did not appear to increase the rate of NADPH oxidation significantly (open circles at 400 µM DHA, and inlet table), but it even decreased at higher concentration (600 µM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…one-tenth of the rate of ascorbate radical reduction and one-third of the rate of electron transfer to heterologous Fd-dependent nitrite reductase in a similar system in Ref. [ 8 ]). On the other hand, the addition of DHA (200–400 µM) did not appear to increase the rate of NADPH oxidation significantly (open circles at 400 µM DHA, and inlet table), but it even decreased at higher concentration (600 µM).…”
Section: Resultsmentioning
confidence: 99%
“…Fd-concentration-dependent NADPH oxidation was observed for both wild-type PfFd and D97Y PfFd, but the activity of the D97Y mutant was roughly half of that of the wild-type PfFd, of which the tendency was similar to the previous results of the electron transfer activity from PfFd and D97Y PfFd (at 5 µM) to a heterologous Fd-dependent enzyme, cyanobacterial nitrite reductase (1.45 and 0.62 NADPH oxidation/FNR/sec., respectively, in Ref. [ 8 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed mutagenesis to substitute PfFd C-terminal residues indicated that an aromatic residue at positions 96 and 97 increased the PfFd-PfFNR binding affinity. A recent study analysing the interaction of PfFd-D193Y and PfFNR showed mutations leading to attenuation of PfFNR function and suggested that this could be associated with the action of artemisinin [13,14]. ARPS10 has a role in apicoplast protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the apicoplast in ART tolerance is generating significant interest. Genetic mutations associated with ART tolerance include fd ( 32 , 73 75 ) and arps10 ( 32 ), which are localized to the apicoplast, and ATG18, which, although it is not localized to the apicoplast, is associated with apicoplast biogenesis ( 76 ), suggestive of an integral role of the apicoplast in ART tolerance. In comparison, fd mutations (D193Y) inserted and removed from K13 mutant and WT strains by Stokes and colleagues ( 77 ) using gene insertion techniques exhibited no apparent effect on parasite survival.…”
Section: Discussionmentioning
confidence: 99%